0788 The effect of CPAP on quality of life in females with mild OSA: Post hoc analysis from the MERGE Randomised Trial. (25th May 2022) - Wimms, Alison; Kelly, Julia; Turnbull, Chris; McMillan, Alison; Craig, Sonia; O'Reilly, John; Nickol, Annabel; Hedley, Emma; Decker, Meredith; Willes, Leslee; Calverley, Peter; Benjafield, Adam; et al.
Abstract: Introduction: The MERGE trial was a multi-centre, randomised, parallel study that showed the beneficial effect of continuous positive airway pressure (CPAP) on quality-of-life in patients with mild obstructive sleep apnea (OSA) (Wimms et al. 2019); findings that have extended the new NICE guidance [Obstructive sleep apnoea/ hypopnoea syndrome and obesity hypoventilation syndrome in over 16s (NG202)].This post-hoc analysis aimed to determine whether differences between the sexes in symptoms and treatment response exist at the mild end of the OSA disease spectrum. Methods: Patients were recruited (Nov 2016 - Feb 2019) to receive either CPAP plus standard care, or standard care alone. Mild OSA was defined as: apnea-hypopnea index (AHI) >5 to ≤15 events/hr. Symptoms and quality-of-life were measured by a range of generic and disease specific questionnaires at baseline and 3 months post CPAP commencement. Results: 233 participants (30% female) were included in this analysis. Females were on average older (mean ± SD) (51.9±10.4 vs 49.8±12.2 years) with higher BMI (32.2±5.0 vs 29.4±3.7 kg/m2) and had a lower AHI than males (median(IQR)) (9.60(6.50 -12.40) vs 10.30(7.10-13.20) events/hour).Females were sleepier (Epworth Sleepiness Score (ESS) (mean ± SD) (11.0±4.2 vs 9.5±4.4)), more fatigued (Fatigue Severity Score (FSS) (42±12.8 vs. 34.4±13.5)) and reported higher levels of anxiety, depression and insomnia. Reported quality-of-life was lower in the SF- 36 mental (41.8±13 vs. 47.3±10.9) and physical components (43.0±11.2 vs. 49.7±9.1), as well as in all individual domains. Females also reported worse scores in the Euroqol 5 Dimensions (EQ-5D) and Functional Outcomes of Sleep Questionnaire (FOSQ), compared to males.All symptoms improved with CPAP use for both sexes, however female patients had larger improvements in the ESS (mean difference(95%CI)) (-5.2 (-6.7, -3.6) vs (-2.0 (-3.0, -1.0)) p=0.0035, and SF-36 vitality (11.7 (7.9, 15.5) vs 5.6 (3.1, 8.1)) p=0.0092. Conclusion: In mild OSA, female patients were more symptomatic and reported worse quality-of-life than males, despite having lower AHIs; all were improved with CPAP treatment. Support (If Any): Funded by ResMed